Sistem pemeriksaan bantuan penglihatan mesin - Ahmad Fadzil Mohamad Hani,; Chu , Jenn Weng (1994)
The development of a machine vision system for inspection of LED devices in industrial environment is discussed in the paper. Methods to detect flaws in LED devices is emphasized. There are two problem statement i.e.: (i) inspect flaws in the LED lead frame at the end of the production line and, (ii) inspect wire loop flaws in the LEDs prior to epoxy encapsulation. Tests were carried out to investigate the capability of the developed machine vision system. Results obtained show a high percentage of success in distinguishing between good and bad LEDs. The generic system described here has a wide application in quality control inspection in the manufacturing environment